Professional Talk discusses lifelines for contractors - Halizan, Mohmood (2021)
KUANTAN, 16 August 2021 - Aligned with the role of liaison between the university, society and industry, the Centre of Industry and Community Network (ICoN), Graduate Development Department, Universiti Malaysia Pahang (UMP) in collaboration with UMP Holdings, Malaysian Malay Contractors Association (PKMM), Pahang Construction Industry Development Board (CIDB), Pahang (CIDB) and Pahang Contractor Services Centre (PKK) organised the Professional Talk Series Webinar Forum - COVID-19 Lifeline for Contractors.